(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
The survey’s immediate results are considered in conjunction with the archaeological evidence. It is argued that the Arran pitchstones offer the potential to examine archaeological sources, usage and movement of material, locally and regionally, at an unusual and perhaps unique level of precision and detail.